2019
DOI: 10.1021/acs.jpcc.9b09445
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Methyl Formate Production Initiated by Photooxidation of Methanol on Rutile TiO2(110) and TiO2(011)-(2 × 1) Surfaces

Abstract: The formation of HCOOCH 3 initiated by photooxidation of CH 3 OH on TiO 2 surfaces is interesting, but the mechanism remains ambiguous. Using thermal desorption spectroscopy and X-ray photoelectron spectroscopy, we herein have comparatively studied the adsorption of HCOOCH 3 on the rutile TiO 2 (110) surface, the coadsorption and photooxidation of CH 3 OH and HCHO on the rutile TiO 2 (110) surface, and the adsorption and photooxidation of CH 3 OH on the rutile TiO 2 ( 011)-(2 × 1) surface. The HCOOCH 3 formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…(ii) HCO* from the further photoreaction of HCHO reacts with CH 3 O ad * 31,32 In order to examine the possibility of MF production by the direct photocatalytic dehydrogenation of methanol and also to clarify the mechanism of MF formation, a series of dehydrogenation experiments and in situ DRIFTS measurements was conducted in an Ar atmosphere over the Pd/TiO 2 catalyst. For comparison, experiments of the oxidative dehydrogenation in a CO 2 atmosphere have been conducted also, and the influence of the atmosphere on MF production is discussed in detail in the present work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) HCO* from the further photoreaction of HCHO reacts with CH 3 O ad * 31,32 In order to examine the possibility of MF production by the direct photocatalytic dehydrogenation of methanol and also to clarify the mechanism of MF formation, a series of dehydrogenation experiments and in situ DRIFTS measurements was conducted in an Ar atmosphere over the Pd/TiO 2 catalyst. For comparison, experiments of the oxidative dehydrogenation in a CO 2 atmosphere have been conducted also, and the influence of the atmosphere on MF production is discussed in detail in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…On the dehydrogenation of methanol, previous experiments and theories have confirmed that first methanol undergoes two steps of dehydrogenation to produce formaldehyde but after that there is a controversy on how formaldehyde is further converted to MF. It has been proposed by different authors that MF may form via different pathways. Dimerization of HCHO , HCO* from the further photoreaction of HCHO reacts with CH 3 O ad * , Reaction of CH 3 O ad * with HCHO, which does not involve the HCO* intermediate …”
Section: Introductionmentioning
confidence: 99%
“…The CH 3 O(a) Ti5c species is photocatalytic active to undergo the C−H bond breaking to form the HCHO(a) species; [7–9] moreover, the photo‐induced oxidative coupling reaction between co‐adsorbed CH 3 O(a) and HCHO(a) at the Ti 5c sites were observed to produce methyl formate (HCOOCH 3 ) [10] . The CH 3 O(a) Ti5C is more photoreactive on rutile TiO 2 (110) surface than on rutile TiO 2 (011)‐(2×1) surface [10d, e] . On anatase TiO 2 (001)‐(1×4) surface, photocatalytic oxidation was observed to occur specifically for the CH 3 O(a) species at the Ti 4c site (CH 3 O(a) Ti4c ) without the further formation of HCOOCH 3 [11] .…”
Section: Introductionmentioning
confidence: 99%
“…These demonstrate that CH 3 O(a) is more photoactive than CH 3 OH-(a) and is photooxidized to HCHO(a). With the irradiation time increasing to 20 min, the CH 3 O(a) coverage only decreases slightly, while the CH 3 OH(a) coverage decreases greatly; meanwhile, the HCHO(a) coverage increases slightly, and the HCOO TiO 2 species with the C 1s binding energy at 289.9 eV 17,30,31 16 This can be attributed to the very small production of HCOOCH 3 .…”
mentioning
confidence: 99%
“…Evolutions of surface species of a 0.55 ML CH 3 OH-covered TiO 2 (100) surface at 110 K under Hg light irradiation were monitored by C 1s XPS (Figure 3A), and variations of observed surface species as a function of the irradiation time were plotted (Figure 3B). Upon a 10 min irradiation, the CH 3 O(a) coverage decreases greatly, while the CH 3 OH(a) coverage decreases slightly; meanwhile, the HCHO(a) species with the C 1s binding energy at 288.7 eV 14,16,17,30,31 emerges. These demonstrate that CH 3 O(a) is more photoactive than CH 3 OH-(a) and is photooxidized to HCHO(a).…”
mentioning
confidence: 99%